Biochar and mineral acid soil phosphorus availability - Haruna, Ahmed Osumanu; Asap, Audrey; Maru, Ali (Universiti Putra Malaysia Press, 2019)
This book provides an essential information for farmers, researchers and students on how biochar and phosphorus fertilisers are optimised to improve soil and crop productivity. It begins with the challenges in managing phosphorus in the mineral acid soils of the tropics and the existing and potential approaches in improving phosphorus availability in tropical agriculture. It also outlines methods of measuring indicators of soil properties and crop productivity. Furthermore, this book presents findings from experiments which optimised the use of biochar and phosphorus fertilisers.